Sistem Pakar Untuk Mendiagnosa Penyakit Lupus Dengan Menggunakan Metode Ripple Down Rules - Maulidya Bella; Nelly Astuti Hasibuan; Suginam Suginam (Journal of Informatics Management and Information Technology, 2021)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease in connective tissue. Autoimmune means that the immune system attacks the body's own tissues. In this SLE, the immune system mainly attacks the cell nucleus. Lupus or SLE comes from the Latin word which means coyote. This term began to be known since the 10th century. Being erythematosus means red. This is to describe a red rash on the skin that resembles the bite of a coyote around the nose and cheeks. So from here the term lupus is still used for Systemic Lupus Erythematosus. Ripple Down Rules (RDR) method is a method for the acquisition of new knowledge from an expert into the system and based on the acquisition of knowledge the system independently makes new rules, where the position of the new rules is adjusted to the rule base of existing rules . In addition, if the expert considers the knowledge entered into the system is not in accordance with his thoughts, then the Ripple Down Rules (RDR) method also allows the expert to delete or replace existing knowledge so that this system can always have the correct and up-to-date knowledge possessed by expert